2011 IEEE 61st Electronic Components and Technology Conference (ECTC) 2011
DOI: 10.1109/ectc.2011.5898680
|View full text |Cite
|
Sign up to set email alerts
|

High density electrical interconnections in liquid crystal polymer (LCP) substrates for retinal and neural prosthesis applications

Abstract: Retinal prostheses implemented by means of electrical stimulation of retinal ganglion cells have been previously demonstrated with 16 and 60 channel microstimulator arrays. Blind patients with severe retinal degeneration (e.g., retinitis pigmentosa (RP) have been able to use these devices to navigate and read large letters. However, to dramatically improve the effectiveness of such prostheses, and to enable a variety of neural stimulation implants, channel densities of 1000 per cm 2 and higher are highly desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…[55]. A recent study has revealed that a helium leakage rate of 1×10 -9 mbar-liter/s (~1×10 -9 atm-cm 3 /s) was measured for a 25-m-thick bulk LCP film, and less than 5×10 -8 mbar-liter/s (~5×10 -8 atm-cm 3 /s) was measured from the LCP film with a feedthrough array; these values are comparable to the leakage rate of glass substrates with metallized vias [56]. LCP encapsulation has been proven to provide superior long-term reliability than that of polyimide and parylene-C through accelerated soak tests [49].…”
Section: Liquid Crystal Polymer (Lcp)mentioning
confidence: 79%
“…[55]. A recent study has revealed that a helium leakage rate of 1×10 -9 mbar-liter/s (~1×10 -9 atm-cm 3 /s) was measured for a 25-m-thick bulk LCP film, and less than 5×10 -8 mbar-liter/s (~5×10 -8 atm-cm 3 /s) was measured from the LCP film with a feedthrough array; these values are comparable to the leakage rate of glass substrates with metallized vias [56]. LCP encapsulation has been proven to provide superior long-term reliability than that of polyimide and parylene-C through accelerated soak tests [49].…”
Section: Liquid Crystal Polymer (Lcp)mentioning
confidence: 79%
“…Although it has been argued whether helium leak tests can be used for polymer-based packages, as stated earlier, there have been a number of helium fine-leak-rate measurements of LCP encapsulations. High-density electrical interconnection feedthroughs, 1024-stimulator channels in a 5 mm × 5 mm area, are realized utilizing a novel fusion bonding process [126]. Helium leak rates of < 5×10 -8 mbar•l s -1 were measured, which is a reliable level compared to the leak rates of glass substrates with metallized vias.…”
Section: Power Consumption and Stimulation Threshold Of Tripolar Stimmentioning
confidence: 99%
“…It has been widely used in commercial products and allows mass production [40], but the manufacturing costs and risk of failure are rapidly increasing for high-density feedthroughs. Many efforts have been dedicated to increase package feedthrough and reliable bonding/joint using new processes and materials [26,27,28,29]. The second option is using one or several layers of biocompatible soft films as a hermetical coating, which has the advantages of being a small-size, light-weight, low-cost, and simple process with high flexibility [41], and has attracted a lot of research interest as an emerging technology enabling high-density, ultra-small medical implants.…”
Section: Packaging and Integrationmentioning
confidence: 99%
“…Due to the biological incompatibility of Si substrate, higher density input/output (I/O) pins and peripheral circuit communication are required. There is a great demand in shrinking the implant size while increasing feedthrough counts [24,25,26,27], which has brought great challenges for packaging. Conventional direct packaging using plastic, metal, or ceramic cannot guarantee the long-term moisture-free environment for high-channel-count electronic devices.…”
Section: Introductionmentioning
confidence: 99%